2020
DOI: 10.3390/jcm9103106
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Ambulatory Management of Patients with Chronic Heart Failure by Protocolized Follow-Up Therapeutic Education and Remote Monitoring Solution: An Original Study in 159 Patients

Abstract: This study sought to determine whether the implementation of regular and structured follow-up of patients with chronic heart failure (CHF), combined with therapeutic education and remote monitoring solution, leads to better management. This was a single-center retrospective study conducted in a cohort of patients with proven CHF who were followed up in the Mulhouse region (France) between January 2016 and December 2017 by the Unité de Suivi des Patients Insuffisants Cardiaques (USICAR) unit. These patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(25 reference statements)
0
2
0
Order By: Relevance
“… 5 However, in nearly 20% of patients, a disconnection occurs between the CIED and manufacturer’s central web server. 6 , 7 This is an important limitation of RM, which has not been well studied systematically. 7 , 8 It has been reported that the identification of patients with device connectivity issues alone can use up to 5 minutes per patient per year and patient calls regarding troubleshooting device connectivity up to 10 minutes per patient per year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 However, in nearly 20% of patients, a disconnection occurs between the CIED and manufacturer’s central web server. 6 , 7 This is an important limitation of RM, which has not been well studied systematically. 7 , 8 It has been reported that the identification of patients with device connectivity issues alone can use up to 5 minutes per patient per year and patient calls regarding troubleshooting device connectivity up to 10 minutes per patient per year.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 This is an important limitation of RM, which has not been well studied systematically. 7 , 8 It has been reported that the identification of patients with device connectivity issues alone can use up to 5 minutes per patient per year and patient calls regarding troubleshooting device connectivity up to 10 minutes per patient per year. 9 We hypothesized that the use of short message service (SMS) would facilitate reconnection in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…3 Remote patient monitoring (RPM) is a telehealth activity that has previously been shown to improve the management of chronic diseases. [4][5][6] Such practices enable healthcare professionals to remotely monitor and deliver care to patients as well as allow patient engagement and access to relevant health-related educational and support systems. In 2019, RPM was recommended for CHF.…”
Section: Introductionmentioning
confidence: 99%